Underwater archaeological research at the Soline site (Korčula) (In situ, 2024)
At the beginning of May 2023, short-term underwater archaeological research was conducted at the Soline site, where a submerged Neolithic site of the Hvar culture is located about 2.5 kilometers southeast of the town of Korčula.
Keywords: Korčula; submerged Neolithic site; Hvar culture